Prevalence of Anaemia and Its Associated Factors among Type 2 Diabetes Mellitus Patients in University of Gondar Comprehensive Specialized Hospital - Sewnet Adem Kebede; Biruk Shalmeno Tusa; Adisu Birhanu Weldesenbet (Anemia)
Background. Anaemia is one of the commonest blood disorders seen in patients with diabetes. In Ethiopia, chronic illnesses are tremendously raising with their complications. But very little research has been conducted, particularly on anaemia among diabetes mellitus (DM) patients. Therefore, this study aimed at assessing the prevalence of anaemia and associated factors among type 2 diabetes mellitus patients in Northwest Ethiopia. Methods. A cross-sectional study design was employed at University of Gondar Comprehensive Specialized Hospital from March 1 to April 15, 2019, among 372 type 2 diabetes mellitus patients (T2DM). Multivariable logistic regression analysis was fitted, and the corresponding adjusted odds ratio (AOR) and 95% CI were used to identify factors associated with anaemia. Level of significance was declared at the p value less than 0.05. Results. The study revealed 8.06% (95% CI: 5.68–11.31%) of the participants were anaemic. Being male (AOR = 2.74, CI: 1.02, 7.38), combined type of treatment (AOR = 8.38, CI: 1.66, 42.25), having diabetes-related microvascular complications (AOR = 3.24, CI: 1.14, 9.26), and hypertension (AOR = 0.01, CI: 0.002, 0.06) were the significant factors associated with anaemia. Conclusions. The finding of the current study revealed low prevalence of anaemia among T2DM patients. Sex, type of treatment, diabetes-related microvascular complications, and hypertension were factors associated with anaemia. Assessment of haemoglobin levels among T2DM patients may help to prevent ensuing microvascular complications. Incorporate anaemia screening into the routine assessment of diabetic complication particularly for those who are hypertensive and took combined treatment to allow early appreciation and treatment of anaemia and later improve the overall care of patients with diabetes.